PERSPEKTIF ARSITEKTUR SURYA DI INDONESIA - Jimmy Priatman (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2000)
Solar energy is a prospective alternative resource due to its existence as a non-polluting source of renewable energy. The potency of solar energy in Indonesia at the belt of equator enables its usage in buildings directly to fulfill human needs. The integrative implementation of solar technology into building emerges specific challenges in architectural design and evolves a new architectural approach which is called